A Systematic Review Study on the Changer Factors of the Quality of life in Cancer Patients - Madmoli, Mostafa (International Research in Medical and Health Sciences, 2019)
Introduction: The rate of mortality from cancer is increasing and at least about 8 million people die every year because of cancer. Unlimited proliferation potential, reduced apoptosis, increased angiogenesis, tissue invasion and metastasis are factors of cancer progression. The purpose of this study was a systematic review study on the changer factors of the quality of life in cancer patients.Materials and Methods: This is a systematic review which in order to achieve the study goal and to improve the accuracy of the study and a comprehensive understanding of this, this integrated overview study was conducted based on the Broome method. The method is done in the form of three steps in the search of texts, data evaluation and data analysis, So, in the search phase, post-retrospective study texts are examined in four stages in terms of inclusion criteria. After obtaining the conditions for entry into the study, the content of the study is evaluated and at the end was done the analysis of the data.Results: In this study, 20 papers were reviewed that The factors that change the quality of life of patients with cancer are shown. The results of one of these studies showed that the hope-centered therapy group, has increased the mean scores of functional domain and quality of life in patients in the intervention group. However, there was no significant difference in symptoms.Conclusion: According to the studied studies, we can say whose therapeutic hope has a significant impact on improving the various dimensions of health-related quality of life in men and women with cancer. Thus, the authorities and managers of the health system of the country, using the results of research in this field, by implementing programs and strategies to create hope-based group therapy interventions for cancer patients, they can improve their quality of life in different areas. The educational pamphlet on occupational therapy programs also affected many of the quality of life of women with breast cancer that it is better to take the necessary measures in this case too.